Albuminuria in Rheumatoid Arthritis: Associations With Rheumatoid Arthritis Characteristics and Subclinical Atherosclerosis. Issue 12 (28th November 2017) - Sammut, Amanda; Shea, Steven; Blumenthal, Roger S.; Szklo, Moyses; Bathon, Joan M.; Polak, Joseph F.; Tracy, Russell; Giles, Jon T.
Abstract : Objective: Albuminuria is a marker for subclinical cardiovascular disease (CVD) in the general population. It is uncertain whether this association is present in patients with rheumatoid arthritis (RA), a population with increased atherosclerosis and CVD events. Methods: Urine albumin from a spot morning collection was measured, and the urine albumin‐to‐creatinine ratio (uACR) was calculated for RA patients and a population‐based sample of demographically matched non‐RA controls. Associations of elevated uACR (≥25 mg/gm for women and ≥17 mg/gm for men) with CVD risk factors and measures of atherosclerosis (coronary artery calcification, ultrasound‐determined maximal intima‐media thickness of the common carotid artery and internal carotid artery [ICA], and the presence of focal plaque in the ICA) were compared cross‐sectionally according to RA status. Results: We compared 196 RA patients with 271 non‐RA controls. Elevated uACR was found in 18% of the RA patients compared with 17% of the controls ( P = 0.89). After adjustment, RA was associated with 57% lower odds of elevated uACR ( P = 0.016). Higher serum creatinine levels and hypertension were both strongly and significantly associated with elevated uACR in the control group but not in the RA group (both P for interaction < 0.05). Among RA characteristics, the adjusted prevalence of elevated uACR among those treated with tumor necrosis factor inhibitors was less than half that among those not so treated (9% versus 20%, respectively; P = 0.047). Conclusion: There was no association in the RA group of elevated uACR with measures of atherosclerosis or with several key cardiometabolic risk factors, which suggests a lower usefulness of elevated uACR as an indicator of subclinical CVD in RA.